2019
DOI: 10.1016/j.molp.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

LOWER TEMPERATURE 1 Enhances ABA Responses and Plant Drought Tolerance by Modulating the Stability and Localization of C2-Domain ABA-Related Proteins in Arabidopsis

Abstract: Plasma membrane-associated abscisic acid (ABA) signal transduction is an integral part of ABA signaling. The C2-domain ABA-related (CAR) proteins play important roles in the recruitment of ABA receptors to the plasma membrane to facilitate ABA signaling. However, how CAR proteins are regulated remains unclear. In this study, we conducted a genetic screen for mutants with altered leaf transpiration and identified an uncharacterized protein, LOWER TEMPERATURE 1 (LOT1), which regulates the dynamic localization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…DroughtSpotter is an automated irrigation gravitropic system. Recently, this system was used to examine the water loss by transpiration of the lot1 Arabidopsis mutant under drought stress and analyze the WUE of the drought-tolerant osphyb rice mutant [21,74]. When we assessed the whole-plant WUE by the ratio between the plant biomass gain (% of initial area) and water irrigated throughout the experimental period, the OsERF115/AP2EREBP110-OE rice exhibited higher WUE than WT plants (Figure 4f).…”
Section: Discussionmentioning
confidence: 99%
“…DroughtSpotter is an automated irrigation gravitropic system. Recently, this system was used to examine the water loss by transpiration of the lot1 Arabidopsis mutant under drought stress and analyze the WUE of the drought-tolerant osphyb rice mutant [21,74]. When we assessed the whole-plant WUE by the ratio between the plant biomass gain (% of initial area) and water irrigated throughout the experimental period, the OsERF115/AP2EREBP110-OE rice exhibited higher WUE than WT plants (Figure 4f).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that StLTP10 physically interacts with ABA receptor PYL4. In Arabidopsis , the C2‐domain ABA‐related (CAR) family of small proteins is involved in recruitment of PYR/PYL/RCAR receptors to the membrane and regulates ABA sensitivity to elicit plant responses to a changing environment (Diaz et al, 2016; Rodriguez et al, 2014; Qin et al, 2019). In this study, the interaction between StLTP10 and PYL4 was detected in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ABA plays a major role in regulating stomatal function in adaptation to various environmental stresses, such as drought, cold, air pollutants, etc. [24][25][26][27] Inadequate stomatal closure at high vapor pressure deficit may be mediated by abscisic acid. 30 In addition, other phytohormones also contribute to stomatal aperture regulation, such as auxin, cytokinin, ethylene and salicylic acid.…”
Section: Sensitivity Of G S To Vpd Variation and The Concentration Ofmentioning
confidence: 99%
“…Increased levels of abscisic acid (ABA) while a plant is under stress promote stomatal closure and/or inhibit stomata opening in order to avoid excessive water loss. [24][25][26][27][28][29] The response of g s to VPD is correlated to the level of ABA. 30 The other phytohormones, including indole-3-acetic acid (IAA) and Gibberellins (GAs), are known to antagonize the effects of ABA on stomatal behavior.…”
Section: Introductionmentioning
confidence: 99%